Estimating CO2 flows in urban parks: knowns and unknowns - Moinel, Caroline; Kuittinen, Matti; Hautamäki, Ranja (Frontiers in Sustainable Cities, 2024)
The life cycle climate impacts of urban parks are poorly known. Whereas vegetation and soils can be carbon sinks, building products, energy use, and processes cause emissions. Several studies acknowledge the need for further assessment of urban parks, especially regarding vegetation, soil organic carbon, management and design, together with the development of supportive tools for climate-wise planning.To deepen our understanding of carbon flows of urban parks, we applied life cycle assessment (LCA) and studied the carbon dioxide (CO2) emissions and removals of five urban parks in Helsinki, Finland. The components of the parks were divided into four categories: site preparation, covering and surface structures, vegetation and growing media, and systems and installations.According to our findings, CO2 emissions ranged from 27.08 to 61.45 kgCO2e/m 2 and CO2 removals from 11.35 to 16.23 kgCO2e/m 2 with uncertainty. Planted woody vegetation and existing forested areas had the highest CO2 uptake among the vegetation types. Moreover, growing media caused on average 35% of total CO2 emissions. As significant volumes of growing media remain necessary to support the growth and establishment of plantings, finding less emission intensive alternatives to peat-based growing medium becomes essential. Other main emissions sources included transportation, and replacements of surface materials, but their dominance is highly dependent on the design, use and maintenance of the park.LCA offers a robust assessment framework for the quantification of greenhouse gas emissions and is evolving towards the including of greenhouse gas removals and storages. However, the inclusion of living organisms would require changes in the mindset of LCA. The level of maturity in the assessment methods differs significantly between the park components. Data and methods are especially lacking for nursery production, maintenance and end-of-life phases of vegetation, soils, and mulches. We also identified uncertainties regarding the estimations of CO2 uptake by woody vegetation, lawns, and meadows due to software limitations and lack of data for local context. Simulating dynamic plantings raises additional questions, together with the forecast of accurate meteorological conditions of a changing climate. This research highlights the need for more holistic life cycle assessment of urban parks to inform low-carbon landscape industries.